Simulation of the Chlorination Process Safety Management System Based on System Dynamics Approach. (2018) - Li, Chen-yang; Wang, Jing-hong; Zhi, You-ran; Wang, Zhi-rong; Gong, Jun-hui
Abstract: It is important to investigate the influence factors of chlorination system safety since the chlorination process is exposed to the risk of chlorine leakages, fires and explosions, which are easy to cause severe casualties. To consider the chlorination process as a complex and dynamic system, a simulation model about the safety of chlorination process is established based on system dynamics. Four modules related to the workers, the management, the laws (and regulations) and the equipment, as well as a mutant factor related to the corrosion degree are comprehensively integrated. Through implementations of a series of scenarios with different inputs, it is found that the proposed SD model can obtain the influence pattern of corrosion degree of equipment in line with common sense, and the work skill has a cumulative, positive impact on system safety, whereas work stress mainly affects system safety over the second half of the life cycle. On the basis of these appreciable influences on the chlorination process safety, some suggestions are also provided for safety management. It is hoped that this work could provide some references for the prevention of accidents in chlorination process and some new ideas for simulation on safety issues in chemical industry.